The Network of Tumor Microtubes: An Improperly Reactivated Neural Cell Network With Stemness Feature for Resistance and Recurrence in Gliomas - Wang, Xinyue; Liang, Jianhao; Sun, Haitao (Frontiers in Oncology, 2022)
Gliomas are known as an incurable brain tumor for the poor prognosis and robust recurrence. In recent years, a cellular subpopulation connected with tumor microtubes (TMs) was identified in brain tumors, which may provide a new angle to explain the invasion, resistance, recurrence and heterogeneity of gliomas. Recently it was demonstrated that the cell subpopulation also tends to express NSC (neural stem cell) marker and shares a lot of features with neural stem cells, which may be seen as an improperly reactivated neural stem-like cell network at later time points of life. The theory of TMs may also provide a new angle to understand the resistance and recurrence mechanisms of gliomas stem cells. In this review, we innovatively focus on the common features between TMs and sprouting axons in morphology, formation and function. Additionally, we summarized the recent progress in the resistance and recurrence mechanisms of gliomas with TMs and explained the incurability and heterogeneity in gliomas with the novel theory. Moreover, we discussed the recently discovered overlap between glioma stem-like cells and TM-connected glioma cells, which may contribute to the understanding of resistant glioma cell subpopulation and the exploration of the new potential therapeutic target for gliomas.